An investigation into the metabolic and cardiovascular effects of phytocannabinoids using in vivo and in vitro techniques - Jadoon, K.A. (2016)
Metabolic syndrome, first described as Syndrome X, includes a cluster of metabolic abnormalities including visceral obesity, insulin resistance, dyslipidaemia and hypertension. The pathophysiology of metabolic syndrome is complex, however, visceral adiposity and insulin resistance are thought to play a central role and both are implicated in the development of type 2 diabetes. Both metabolic syndrome and type 2 diabetes increase the risk of cardiovascular disease, by initiating and accelerating the progression of atherosclerosis, the hallmark of cardiovascular disease. Chronic low-grade inflammation of adipose tissue and vascular endothelium is well documented in type 2 diabetes and associated cardiovascular disease. In addition, stress has also been identified as one of the factors that increases the risk of cardiovascular disease.